2011
DOI: 10.2174/156720511797633197
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β Peptide Levels Increase in Brain of AβPP Swedish Mice after Exposure to Chlorpyrifos

Abstract: Chlorpyrifos (CPF) is an organophosphate pesticide widely used in intensive agriculture. Various studies have demonstrated delayed neurotoxic effects in adult mammals after acute CPF exposure. This pesticide induces oxidative stress and neuronal damage, which suggests a possible relationship between CPF exposure and Alzheimer's disease (AD). In the present study, we examined in a mice model of AD, long-term changes in the behavior and brain levels of amyloid β after acute CPF exposure. Fifty mg/kg of CPF were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Our present investigation reveals that chronic oral exposure to CPF increased the search velocity in these subjects, which may explain their apparent improvement. In animal models, activity after adult exposure to CPF has been reported to either increase [51] or decrease [63] in Tg2576 mice. In a recent study, increased vertical activity and a trend towards an anxiety trait were observed five months after repeated exposure to CPF in Tg2576 adult male mice [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our present investigation reveals that chronic oral exposure to CPF increased the search velocity in these subjects, which may explain their apparent improvement. In animal models, activity after adult exposure to CPF has been reported to either increase [51] or decrease [63] in Tg2576 mice. In a recent study, increased vertical activity and a trend towards an anxiety trait were observed five months after repeated exposure to CPF in Tg2576 adult male mice [51].…”
Section: Discussionmentioning
confidence: 99%
“…To date numerous studies have endorsed the neurotoxic and behavioral effects of CPF in both human [6,20,21,55,62] and animal models [10,37,40,63,67]. CPF exerts its insecticidal activity by irreversibly inhibiting cholinesterases (ChE) and disrupting cholinergic function in the nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, previous in vitro studies have shown that muscarinic agonists (primarily M1 and M3, but also M4) promote cell survival (Budd et al, 2003(Budd et al, , 2004De Sarno et al, 2003;Lindenboim et al, 1995). Besides, CPF has been described to increase Ab protein production (Salazar et al, 2011), tau and GSK-3b hyperphosphorilation (Chen et al, 2012;Torres-Altoro et al, 2011), both having been related with induction of cell death in basal forebrain cholinergic neurons and AD (Kar et al, 2004), and also for being able to mediate this effect. Moreover, CPF also is able to induce reactive oxygen species (ROS) formation (Ki et al, 2013), and they Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Several in vitro studies have documented that dichlorodiphenyltrichloroethane (DDT) significantly increases levels of amyloid-β precursor protein (Aβ PP) and β -site Aβ PP-cleaving enzyme 1(BACE1), impairing the clearance and extracellular degradation of amyloid-β peptides 28,29 . An in vivo study revealed that some pesticides may disrupt metabolic pathways involved in the homeostasis of amyloid-β , causing a significant increase in amyloid-β levels in the cortex and hippocampus, as well as increased memory loss and reduced motor activity in experimental animals 30 . Thus, some researchers have hypothesized that pesticide exposure is a potential risk factor for AD, and this hypothesis has been further validated by the results of several epidemiological studies 12,18 .…”
Section: Discussionmentioning
confidence: 99%